Development of the continuous curvilinear lenticulerrhexis technique for small incision lenticule extraction - Zhao, Yu; Knorz, Michael C. (Journal of refractive surgery, 2015)
PURPOSE: To develop and evaluate the new continuous curvilinear lenticulerrhexis (CCL) technique for small incision lenticule extraction. METHODS: Thirty-one eyes of 20 patients with myopia were included in the study. The CCL technique for lenticule extraction was developed and used in 16 eyes of 10 patients (CCL group). The traditional technique of lenticule extraction was used in 15 eyes of 10 patients (traditional group). Uncorrected and corrected distance visual acuity, manifest refraction, lenticule quality, the duration of the extraction procedure, microdistorsions in Bowman’s layer under optical coherence tomography (Optovue OCT; Optovue, Inc., Fremont, CA), and adverse events were evaluated at 1 day and 1 month postoperatively. RESULTS: At the first postoperative month, all eyes in both groups had an uncorrected distance visual acuity of 1.0 or better. The safety indices were 1.12 and 1.09 for the CCL and traditional groups, respectively. The efficacy indices were 1.06 and 1.09 for the CCL and traditional groups, respectively. All lenticules in the CCL group had intact, round margins, whereas one lenticule in the traditional group had a microdefect margin. There was no statistically significant difference in duration of lenticule extraction or microdistorsions in Bowman’s layer. No eyes in the CCL group developed diffuse lamellar keratitis, as compared to one eye in the traditional group. CONCLUSIONS: The CCL technique exhibited excellent safety and efficacy for myopia correction, suggesting CCL is a promising technique that merits further development and study.
Gesehen am 06.09.2017